Joseph Stanley-Brown papers - Stanley-Brown, Joseph, 1858-1941.
Correspondence, reports, briefs, notes, family papers, newspaper clippings, printed matter, and other papers relating to Stanley-Brown's service as private secretary to Presidents James A. Garfield and Chester Alan Arthur, work in connection with the arbitration between the U.S. and Great Britain over sealing in the Bering Sea and on the Pribilof Islands, and tenure as a superintendent in Alaska for the North American Commercial Company. Also includes material pertaining to Stanley-Brown's family and to his genealogical studies. Individuals represented in the papers include Henry Wood Elliott, John Watson Foster, George Kennan, Robert Lansing, H.H. McIntyre, and Thomas C. Mendenhall.
Library of Congress Rare Book and Special Collections Division.
Library of Congress Prints and Photographs Division.
Library of Congress Geography and Map Division.
Presidential secretary, civil servant, and banker.
Collection material in English, with Russian. Much of the collection is written in shorthand.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arthur, Chester Alan, -- 1829-1886.; Elliott, Henry Wood, -- 1846-1930.; Foster, John Watson, -- 1836-1917.; Garfield, James A. -- 1831-1881.; Kennan, George, -- 1845-1924.; Lansing, Robert, -- 1864-1928.; McIntyre, H. H. -- 1844-1906.; Mendenhall, Thomas C. -- 1841-1924.; Brown family; Stanley family; Stanley-Brown family; North American Commercial Company; Arbitration (International law); Sealing -- Alaska -- Pribilof Islands; Sealing -- Bering Sea; Alaska -- History; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- Great Britain; Bankers; Civil servants; Secretaries, Presidential